From collective efficacy and negative emotions toward management and conservation of wetlands: the mediating role of social identity - Valizadeh, Naser; Karimi, Vahid; Bazrafkan, Khadijeh; Azadi, Hossein; Azarm, Hassan (Frontiers in Psychology, 2025)
Wetlands are among the most valuable natural resources on Earth. However, many have been destroyed in recent decades. One suggested solution for their sustainable use is the creation of collective management and protection strategies. These measures would involve stakeholders at various levels. Therefore, in this study, the encapsulation model of social identity in collective action is used to increase understanding of how participation in the collective management and protection of wetlands is strengthened. The aim of this study was to examine farmers’ willingness to engage in collective protection and management activities for Helleh Wetland. To achieve this, a cross-sectional survey was conducted among farmers living near the Helleh Wetland in Iran. The results indicated that the encapsulation model of social identity in collective action effectively explained the farmers’ intentions to participate in the collective management and protection of the wetland. According to the results, social identity and negative emotions had significant relationships with the intention toward participation in collective management and protection. Similarly, collective efficacy was also found to be related to the intention toward participation in collective management and protection. The results also indicated that using the encapsulation model of social identity in collective action to motivate farmers to participate in wetland management and protection can be effective. However, this approach will be most successful if environmental management authorities prioritize addressing and removing past negative experiences related to participation. This study offers insights into the socio-psychological factors that influence intentions to participate in collective wetland management and conservation. The findings also provide valuable implications for managers, policymakers, and decision-makers, helping them to effectively encourage participation in collective wetland management and conservation.